Screening Out Reactivity-Promoting Candidates for γ-Ca2SiO4 Carbonation by First-Principles Calculations - Tao, Yong; Mu, Yuandong; Zhang, Wenqin; Wang, Fazhou (Frontiers in Materials, 2020)
γ-Ca2SiO4 as a promising carbonation-activated cementitious material features an attractive capacity of carbon sequestration. Improving the carbonation reactivity of γ-Ca2SiO4 is of great significance for its practical application. In this paper, the first-principles calculations are performed to single out potential candidates for carbonation activation from a series of dopants. Electronic structure analyses reveal that the carbonation reactivity is related to the reactive site distribution and the binding strength of γ-Ca2SiO4 crystal. Ba, P, and F elements are found to decrease the overall binding strength of γ-Ca2SiO4 crystal, which benefits the dissolution of ions from the crystal to take part in carbonation reactions. The theoretical conjectures are validated by designed and previous experiments, which confirms the first-principles based method to effectively guide our experimental investigation.